Camels, climate, and capital: Subverting the narrative of pastoral sustainability - Mohamed, Tahira Shariff; Jilo, Roba Bulga (The Elephant, 2025)
As pastoralist communities seek ways of adapting to climate change, camel rearing is taking precedence, with the sale of camel products providing sustainable livelihoods in regions facing recurrent drought.